Pre-clinical imaging centers: design, animal handling and examples - Stout, David (Henry Stewart Talks, 2010)
Designing small animal imaging facilities, Imaging methods, Regulatory oversight, Infectious and carcinogenic agents, UCLA imaging experiments, Animal handling training, Systems and personnel requirements, Planning the flow of the workspace, Database and image management, Archiving and data retrieval, Operational considerations, Preclinical molecular imaging: why use animals?, Experimental design issues, Anaesthesia, Heating options, Blood sampling, Case studies, Optical imaging, Getting it right